Correlation Between Human Development Index and Economic Growth of Major Oil and Gas Producers - PEKARČÍKOVÁ, Kateřina; PRACHAŘOVÁ, Lenka (GeoScience Engineering, 2023)
This paper examines the correlation between the Human Development Index (HDI) and the economic growth of the top oil and gas-producing countries. The 14 largest producers selected for analysis are the USA, Russia, Saudi Arabia, Canada, Iraq, China, United Arab Emirates, Brazil, Kuwait, Iran, Qatar, Australia, Norway, and Algeria. These countries include both developed and developing countries. It is also important to examine the issues mentioned from this perspective. The Pearson correlation coefficient is used for the analysis, and the relationship between economic growth and HDI between 1980 and 2020 is examined. The selected data analysed is almost complete except for a few missing values, for example, in the case of Russia, Saudi Arabia, Canada and Iraq. However, even this fact may slightly distort the analysis. The results show a correlation for all the top producers examined. The highest correlation, very strongly positive, was observed in the case of the USA. Very strong positive correlations were also found for China, Canada, Australia, Russia, Norway, and Algeria. The lowest correlation values were recorded for Iraq, Kuwait, and the United Arab Emirates. The analysis can be used as a basis for further analysis. Keywords: Economic growth; Gas; Gross Domestic Product (GDP); Human Development Index (HDI); Oil; Pearson correlation coefficient.